Mathematical Anxiety among Primary Education Degree Students in the Post-Pandemic Era: A Case Study - María Teresa Costado Dios; José Carlos Piñero Charlo (MDPI AG, 2024)
The study of the affective domain has grown in relevance ever since educators and researchers showed its influence in the process of teaching and learning, playing a fundamental role in the evolution of student learning. Anxiety is one component of the affective domain. The study of mathematical anxiety in pre-service primary teachers at university is the focus of this study. We analyse mathematical anxiety by examining specific data from the sample (age, gender, the subjects they studied in upper-secondary education, and academic performance). One hundred and nineteen students from the Primary Education degree completed the mathematical anxiety questionnaire, obtaining an average anxiety score considered negative (3.08 above the neutral value of 3). The results show a high anxiety toward examinations (3.68) and a negative relation with academic performance. Furthermore, the results show that women, 19-year-old university students, and those from a humanities-based upper-secondary education present greater levels of anxiety than men, older students, or students from other areas of upper-secondary education, respectively. All values of mathematical anxiety are higher than pre-pandemic levels. We can conclude from the studied sample that the students show low-medium global anxiety over mathematics, medium anxiety over problem solving, and high anxiety about exams.